
几道分解因式题
ax²;-16ay²-2a³+12a²-18aa²(x-y)-4b²(x-y)(x+2)(x-6)+16(x&...
ax²;-16ay²
-2a³+12a² -18a
a²(x-y)-4b²(x-y)
(x+2)(x-6)+16
(x²+y²)²-4x²y² 展开
-2a³+12a² -18a
a²(x-y)-4b²(x-y)
(x+2)(x-6)+16
(x²+y²)²-4x²y² 展开
展开全部
ax²;-16ay²=a(x-4y)(x+4y)
-2a³+12a² -18a=-2a(a²-6a+9)==-2a(a+3)²
a²(x-y)-4b²(x-y)=(x-y)(a²-4b²)=(x+y)(a+2b)(a-2b)
(x+2)(x-6)+16=x²-4x+4=(x-2)²
(x²+y²)²-4x²y²=(x²+y²-2xy)(x²+y²+2xy)=(x-y)²(x+y)²
-2a³+12a² -18a=-2a(a²-6a+9)==-2a(a+3)²
a²(x-y)-4b²(x-y)=(x-y)(a²-4b²)=(x+y)(a+2b)(a-2b)
(x+2)(x-6)+16=x²-4x+4=(x-2)²
(x²+y²)²-4x²y²=(x²+y²-2xy)(x²+y²+2xy)=(x-y)²(x+y)²
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询